2015
DOI: 10.1007/s10734-015-9934-2
|View full text |Cite
|
Sign up to set email alerts
|

Understanding graduate school aspirations: the effect of good teaching practices

Abstract: This study examined the effects of good teaching practices on post-baccalaureate degree aspirations using logistic regression techniques on a multi-institutional, longitudinal sample of students at four-year colleges and universities. Using College Choice and College Outcomes models as a theoretical foundation, I examined whether eight good teaching practices (non-classroom interactions with faculty, prompt feedback, frequency of interactions with faculty, teaching clarity and organization, challenging classes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 95 publications
(211 reference statements)
1
24
0
1
Order By: Relevance
“…However, this was only the case for African American undergraduate students, identifying as Hispanic did not significantly change the odds of applying to graduate or professional school as compared with White students. Hanson et al (2016) found a similar pattern in that undergraduate students whom identified as a Student of Color had a positive effect and increased the odds of having postbaccalaureate degree aspirations. In addition, gender differences have been observed when examining aspirations to pursue graduate education.…”
Section: Review Of the Literaturementioning
confidence: 59%
See 2 more Smart Citations
“…However, this was only the case for African American undergraduate students, identifying as Hispanic did not significantly change the odds of applying to graduate or professional school as compared with White students. Hanson et al (2016) found a similar pattern in that undergraduate students whom identified as a Student of Color had a positive effect and increased the odds of having postbaccalaureate degree aspirations. In addition, gender differences have been observed when examining aspirations to pursue graduate education.…”
Section: Review Of the Literaturementioning
confidence: 59%
“…National trends of entering college students in 2006 showed that about 40% of Latinas/os aspired to earn a master’s, but only 34.1% of Latinos aspired to earn a PhD, MD, JD compared with 39.6% of Latinas (Hurtado et al, 2008). Precollege aspirations are particularly important to consider as studies have shown the strong relationship between these initial goals and aspirations by the end of college (Hanson, Paulsen, & Pascarella, 2016; Pascarella et al, 2004).…”
Section: Review Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Higher education aspirations are on the rise and are often treated as an expectation for most high school graduates (Eagan et al, 2014). With the increasing number of students interested in post-baccalaureate graduate education, researchers, policy-makers, and educators have become particularly interested in what experiences encourage or discourage students from considering postbaccalaureate education (Hanson, Paulsen, & Pascarella, 2016;Millet, 2003). Previous research on graduate degree aspirations focused primarily on American students' background characteristics such as race, sex, and socioeconomic status (Pascarella, Wolniak, Pierson, & Flowers, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…-Student-faculty interactions within and out of classes promote student commitment and motivation [7], [9].…”
Section: Encourage Contact Between Students Andmentioning
confidence: 99%